Analysis of time lapse seismic signal for an EOR and CCS site, Cranfield, MS - Ditkof, J.; Meckel, T.; Hovorka, S.; Caspari, Eva; Pevzner, Roman; Urosevic, Milovan (SEG, 2012)
The Cranfield, MS EOR field site has been under CO2 flood by Denbury Onshore, LLC since 2008. More than 3 million tons of CO2 has been injected. Time-lapse 3D surface seismic data displayed a readily observable signal related to CO2 injection into the lower Tuscaloosa Formation. The intensity and the spatial distribution of time-lapse (TL) signal required further analysis. For that purpose, we carried out fluid substitution analysis, followed by volumes cross-equalization, well ties, and acoustic impedance inversions. A Gassmann workflow was used to predict the response to injected CO2 at two well locations. The 31F-2 observation well, located in a detailed area of study (DAS), was used to compare the results of time-lapse sonic data with fluid substitution results. The objective was to predict a post-injection saturation curve. A second well, well 28-1, was used to help predict an acoustic impedance change in the reservoir to use for subsequent inversion. Finally, a model based inversion was performed to quantify the impedance change between two cross-equalized time-lapse data sets. The acoustic impedance (AI) difference obtained through the inversion process is higher than that predicted for in the 28-1 injection well. The time-lapse AI signal is however in agreement with the large velocity change computed from the time delay along the marker horizon below the reservoir.